2019
DOI: 10.1097/sih.0000000000000400
|View full text |Cite
|
Sign up to set email alerts
|

“It's Not an Acting Job … Don't Underestimate What a Simulated Patient Does”: A Qualitative Study Exploring the Perspectives of Simulated Patients in Health Professions Education

Abstract: Introduction Simulated patients (SPs) are individuals who have learned to realistically portray patient roles in health professional education. Program recommendations are increasing for simulation programs, and as key stakeholders, SPs' perspectives seem underrepresented. The aim of the study was to explore the experiences, perspectives, and practices of SPs to gain insights on topics of importance to SPs and inform program recommendations. Methods An … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 31 publications
2
31
2
Order By: Relevance
“…Experiences of physical discomfort while portraying a patient role (see subthemes 1.3 and 3.3) appear similar to those reported in the wider SP literature. 23 26 However, instances of psychological disturbance from portraying a patient role were less prevalent in this study compared with those reported by professional SPs. 25 26 The most challenging components of peer simulation for students appeared to be related to acting as the peer-therapist.…”
Section: Discussioncontrasting
confidence: 67%
See 3 more Smart Citations
“…Experiences of physical discomfort while portraying a patient role (see subthemes 1.3 and 3.3) appear similar to those reported in the wider SP literature. 23 26 However, instances of psychological disturbance from portraying a patient role were less prevalent in this study compared with those reported by professional SPs. 25 26 The most challenging components of peer simulation for students appeared to be related to acting as the peer-therapist.…”
Section: Discussioncontrasting
confidence: 67%
“…23 26 However, instances of psychological disturbance from portraying a patient role were less prevalent in this study compared with those reported by professional SPs. 25 26 The most challenging components of peer simulation for students appeared to be related to acting as the peer-therapist. This may have been because the patient roles were not psychologically or emotionally complex.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…Patient simulation has been used widely in health professions education. [1][2][3] The University of North Carolina at Chapel Hill (UNC-CH) Adams School of Dentistry has embraced patient simulations as a core component of student assessment. Students complete in-person interviews with standardized patient (SP) actors to practice interviewing skills and develop deeper diagnostic reasoning and critical thinking.…”
Section: Problemmentioning
confidence: 99%